Juridic Aspects of the Criminal Action of Child Neglection by Parents - Jumriani Nawawi (Al-Bayyinah, 2022)
This research is focused on how positive law enforcement is in providing protection to children from the criminal act of neglection. This study aims to determine the phenomenon related to conflict that often occurs in society in the form of neglect of parents to their children. Protection of children from violent criminal acts in the form of neglection from parents has been strictly regulated in regulations. This type of research is normative juridical research. The research was conducted qualitatively by relying on library research. The results showed that the forms of child neglect were physical neglect, educational neglect, emotional neglect, and medical neglect. Regarding the neglect of children by their parents, they should be legally accountable. The criminal act of neglecting children by their parents is very clearly regulated in the Child Protection Law Number 35 of 2014 concerning Child Protection and the Criminal Procedure Code.